Ecotourism: Examining the Driving Factors of Revisit Intention in Nature-Based Tourism in Labuhanbatu - Ade Parlaungan Nasution; Muhammad Yasir Arafat Pohan; Fadzil Hanafi Asnora (ARRUS Journal of Social Sciences and Humanities, 2026)
This research aims to analyze the factors influencing tourists' revisit intention to nature-based tourism destinations in Labuhanbatu Regency, which has great potential for ecotourism development but faces challenges in fostering tourist loyalty. Using a quantitative approach with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method, this study examines the influence of tourist satisfaction, perceived destination sustainability, and destination image on revisit intention. The results show that all three variables have a positive and significant effect on revisit intention, with destination image as the strongest predictor, followed by tourist satisfaction, and perceived destination sustainability. The findings indicate that to increase revisit intention, destination managers need to focus on three main aspects: improving the quality of the tourism experience to create satisfaction, building and strengthening destination image through effective branding strategies and marketing communication, and implementing and communicating tangible sustainable tourism practices. This research provides theoretical contributions by integrating various theoretical perspectives (expectancy-disconfirmation theory, image formation theory, and theory of planned behavior) in the context of Indonesian ecotourism, and provides practical implications for Labuhanbatu tourism stakeholders in designing sustainable and competitive nature-based tourism.